Sistem Informasi Pemesanan Tiket Berbasis Web Pada Agen "Rahayu Tiket" - Ikhsan, Muhammad; Karindra, Aditya Akbar Rizky; Widayat, Jonathan Setya Widayat Setya; Santi, Indyah Hartami (Arcitech: Journal of Computer Science and Artificial Intelligence, 2024)
Information technology has become an integral part of the ticket agent industry, enabling travel agents to improve operational efficiency and provide better service to customers. This research aims to investigate and implement a web-based ticket booking system at the "Rahayu" travel agent with the aim of expanding the geographical scope of their services. By combining related literature and relevant web references, we designed, developed and tested a ticket booking system prototype. The results show that implementing this system can increase customer comfort, operational efficiency and order accuracy, further expanding customer coverage